Managing risk in corporate groups: Limited liability, asset partitioning, and risk compartmentalization - Belenzon, Sharon; Lee, Honggi; Patacconi, Andrea (Strategic Management Journal, 2023)
Abstract Research Summary Limited liability enables corporate parents to avoid financial responsibility of their subsidiaries. However, courts can disregard separate legal personality, “pierce the corporate veil,” and impose the debts of a subsidiary on its parent—an exception referred to as “enterprise liability.” We argue that in countries with weak enterprise liability, groups can better compartmentalize risks by incorporating more of their units as legally independent subsidiaries. Weaker enterprise liability may also induce headquarters to delegate more decision‐making authority to their subsidiaries, invest more, and expand faster, although failure rates could rise. Using data from 16 countries across the Americas, Asia, and Europe, we provide evidence supporting these predictions. This paper highlights two channels—risk compartmentalization and subsidiary autonomy—through which limited liability laws affect organizational outcomes. Managerial Summary Limited liability is a key attribute of the corporate form. However, when the owner of a corporation is another corporation (as in corporate groups), a key justification for limited liability—to protect small, passive investors from unlimited losses—is severely weakened. We examine how variation in parent limited liability protections for subsidiaries across countries affect firm boundaries, internal organization, and performance. In countries with strong limited liability protections, groups partition their assets more finely into legally independent subsidiaries and grant their subsidiaries more autonomy. They also invest more and grow faster, although they experience higher rates of significant revenue declines. Our findings suggest that limited liability laws play a central role in shaping organizational structure and performance.